Collaboration Meeting with IYRES Ministry of Youth and Sports - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 26 July 2021 - This collaboration was held virtually between FK and Institute for Youth Research Malaysia (IYRES).